A dark and stormy murder : a writer's apprentice mystery - Buckley, Julia, 1964- (Buckley, Julia, 1964- Writer's apprentice mysteries., 2016)
Camilla Graham's bestselling suspense novels inspired Lena London to become a writer, so when she lands a job as Camilla's new assistant, she can't believe her luck. Not only will she help her idol craft an enchanting new mystery, she'll get to live rent-free in Camilla's gorgeous Victorian home in the quaint town of Blue Lake, Indiana. But Lena's fortune soon changes for the worse. First, she lands in the center of small town gossip for befriending the local recluse. Then she stumbles across one thing that a Camilla Graham novel is never without: a dead body, found on her new boss's lakefront property.